Kompor Minyak Jelantah: Kinerja dan Keberlanjutan dalam Pemanasan Air Rumah Tangga - Suwarno, Djoko Untoro; Harini, Wuri; Widyastuti, Wiwien; Sriwindono, Haris; Puwoto, Lukas (Seminar Nasional Penelitian dan Abdimas, 2024)
Abstract — This study evaluates the efficiency and sustainability of using a waste cooking oil stove for heating water in a household setting. In the tests conducted, the waste cooking oil stove successfully heated 500 ml of water from 30°C to 100°C in 9 minutes, with a heating power of approximately 270 watts. The consumption of waste cooking oil as fuel was recorded at 100 ml per hour of operation, demonstrating the potential of waste cooking oil as an economical and eco-friendly alternative fuel. However, the use of tissue paper as an initial heating aid produced residue that required routine cleaning of the stove's burner. It is recommended to develop a more efficient and cleaner initial heating mechanism, such as integrating an electric heating element or using ignition materials that do not leave residue. Additionally, designing an easily cleanable burner and optimizing airflow are suggested to improve user convenience and efficiency. With the implementation of these recommendations, the waste cooking oil stove can become a more practical and environmentally friendly fuel solution for households.   Abstrak—Penelitian ini mengevaluasi efisiensi dan keberlanjutan penggunaan kompor minyak jelantah untuk pemanasan air dalam skala rumah tangga. Dalam pengujian, kompor minyak jelantah berhasil memanaskan 500 ml air dari suhu 30°C hingga 100°C dalam waktu 9 menit, dengan daya pemanasan sekitar 270 watt. Konsumsi minyak jelantah sebagai bahan bakar tercatat sebesar 100 ml per jam operasi, menunjukkan potensi penggunaan minyak jelantah sebagai alternatif bahan bakar yang hemat dan ramah lingkungan. Namun, penggunaan tisu sebagai pemanas awal menimbulkan residu yang memerlukan pembersihan rutin pada tungku kompor. Disarankan pengembangan mekanisme pemanasan awal yang lebih bersih dan efisien, seperti integrasi elemen pemanas listrik atau penggunaan bahan pemantik yang tidak meninggalkan residu. Desain tungku yang mudah dibersihkan dan optimasi aliran udara juga diusulkan untuk meningkatkan kenyamanan dan efisiensi penggunaan. Dengan penerapan saran-saran ini, diharapkan kompor minyak jelantah dapat menjadi solusi bahan bakar yang lebih praktis dan ramah lingkungan bagi masyarakat.